2021
DOI: 10.3389/fpsyg.2020.610414
|View full text |Cite
|
Sign up to set email alerts
|

Justice Sensitivity in Middle Childhood: A Replication and Extension of Findings

Abstract: Previous research showed justice sensitivity (JS) – the tendency to perceive and negatively respond to injustice as a victim, observer, or perpetrator – to be reliably and validly measurable in middle childhood, but unexpected findings concerning mean values and measurement invariance (MI) require replication, and retest reliabilities, longitudinal relations with prosocial and aggressive behavior, and relations with teacher ratings are currently unknown. This study, therefore, examined mean values, factor stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Regarding the relations between the outcome measures and the JS subscales, differential relations can be expected as well. In previous research, victim JS predicted more aggressive behavior in children, adolescents, and adults (Bondü, 2018; Bondü & Richter, 2016; Strauß et al, 2020), adults’ uncooperative behavior in experimental games (Fetchenhauer & Huang, 2004; Gollwitzer et al, 2009), less prosocial behavior in children (Bondü & Kleinfeldt, 2021; Strauß et al, 2020), less solidarity with unlucky others or countries in need (Stavrova & Schlösser, 2015), and less moral courage (Niesta Kayser et al, 2010) in adults. Individuals high in victim JS even tended to justify own norm transgressions (Gollwitzer et al, 2012).…”
Section: Justice Sensitivitymentioning
confidence: 89%
See 3 more Smart Citations
“…Regarding the relations between the outcome measures and the JS subscales, differential relations can be expected as well. In previous research, victim JS predicted more aggressive behavior in children, adolescents, and adults (Bondü, 2018; Bondü & Richter, 2016; Strauß et al, 2020), adults’ uncooperative behavior in experimental games (Fetchenhauer & Huang, 2004; Gollwitzer et al, 2009), less prosocial behavior in children (Bondü & Kleinfeldt, 2021; Strauß et al, 2020), less solidarity with unlucky others or countries in need (Stavrova & Schlösser, 2015), and less moral courage (Niesta Kayser et al, 2010) in adults. Individuals high in victim JS even tended to justify own norm transgressions (Gollwitzer et al, 2012).…”
Section: Justice Sensitivitymentioning
confidence: 89%
“…The negative effects of victim JS were explained by exaggerated perceptions of others’ untrustworthiness, concerns about being taken advantage of, and/or generalized expectations of unfair treatment (Bondü, 2018; Fetchenhauer & Huang, 2004; Gollwitzer et al, 2015). In addition, despite positive relations with ToM and empathy (Edele et al, 2013; Schmitt et al, 2005; Strauß et al, 2020), victim JS showed negative relations with affective and behavioral self‐regulation that may hamper the adequate execution of prosocial behavior (Bondü & Kleinfeldt, 2021). Given the negative relations with prosocial behavior and positive relations with aggression, the interest in justice for one's own sake, justifications of own norm transgressions, and general expectations of norm transgression in others, victim JS should positively relate to more egoistic and hedonistic reasoning (indicating less advanced moral reasoning) in moral dilemma situations and positive emotion attribution in norm transgressors (happy victimizer).…”
Section: Justice Sensitivitymentioning
confidence: 99%
See 2 more Smart Citations
“…Response options ranged from 0 = not at all true to 3/5 = exactly true . Evidence for the reliability and validity of the measures was provided (Bondü & Kleinfeldt, 2021; Strauß et al, 2020). We computed separate mean scores for all three JS perspectives and a combined altruistic JS score from observer and perpetrator JS.…”
Section: Methodsmentioning
confidence: 99%